2011
DOI: 10.1007/s10008-011-1470-0
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical characterization of praseodymium centers in Pr x Zr1−x O2 zirconias using electrocatalysis and photoelectrocatalysis

Abstract: The voltammetry of nanoparticles and scanning electrochemical microscopy are applied to characterize praseodymium centers in tetragonal and monoclinic zirconias, doped with praseodymium ions (Pr x Zr 1−x O 2 ), prepared via sol-gel routes. Doped zirconia nanoparticles were synthesized by a sol-gel liquid-phase route and characterized by different techniques, including X-ray diffraction powder pattern, ultraviolet-visible diffuse reflectance spectroscopy, infrared spectroscopy, and transmission electron microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 62 publications
(65 reference statements)
0
7
0
Order By: Relevance
“…The experimental procedure used in the preparation of Fe-containing zirconia gels, Fe x Zr 1Àx O 2 , with compositions in the range 0 r x r 0.15, was previously described in the preparation of other metal-doped zirconia. 12,29 Basically the procedure is as follows. To a mixture of acetylacetone (acacH, C 5 H 8 O 2 ) and absolute ethanol (EtOH, C 2 H 5 OH) kept under N 2 inert atmosphere were added the required amounts of zirconium n-propoxide (ZnP, Zr(OC 3 H 7 ) 4 ) and iron acetylacetonate (Fe(acac) 3 , FeC 15 H 24 O 6 ).…”
Section: Synthesis Of Fe-containing Zro 2 Gelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental procedure used in the preparation of Fe-containing zirconia gels, Fe x Zr 1Àx O 2 , with compositions in the range 0 r x r 0.15, was previously described in the preparation of other metal-doped zirconia. 12,29 Basically the procedure is as follows. To a mixture of acetylacetone (acacH, C 5 H 8 O 2 ) and absolute ethanol (EtOH, C 2 H 5 OH) kept under N 2 inert atmosphere were added the required amounts of zirconium n-propoxide (ZnP, Zr(OC 3 H 7 ) 4 ) and iron acetylacetonate (Fe(acac) 3 , FeC 15 H 24 O 6 ).…”
Section: Synthesis Of Fe-containing Zro 2 Gelsmentioning
confidence: 99%
“…VMP is a solid-state electrochemical technique developed by Scholz et al [25][26][27] which provides information on the chemical and mineralogical compositions of sparingly soluble solids. In previous reports, we have already used this technique for obtaining chemical and structural, 13,28 and electrocatalytic information 28,29 and analytical applications 11,12 of V-and Pr-doped zirconia.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the enhanced electrochemical performance of NiFeCoPrO-Au/NF can be attributed to the incorporation of the Pr dopant, , the support of the gold bottom coating, and the ultrathin amorphous nanostructure of the active materials. , …”
Section: Resultsmentioning
confidence: 99%
“…Solid-state electrochemical experiments were performed by mechanically transferring small amounts of the solid specimens to the surface of paraffin-impregnated graphite electrodes following the procedures already reported. 22,23 Cyclic (CV) and square wave voltammetric measurements (SWV) were performed at 298 ± 1 K in a conventional three-electrode cell under argon atmosphere using a CH I660 potentiostat coupled to a conventional three-electrode cell with Pt auxiliary electrode and AgCl (3M NaCl)/Ag reference electrode. NaNO 2 (Merck) in concentrations between 1.0 mM and 0.15 M and 0.50 M acetic acid/sodium acetate (HAc/NaAc, Panreac) buffer (pH 4.75), 0.10 M potassium phosphate buffer (pH 7.00) and 0.10 M NaCl were used as supporting electrolytes.…”
Section: Methodsmentioning
confidence: 99%
“…14 Previous results confirmed that preparation of nanoparticulate V-and Zr-doped zirconias, with relatively narrow particle size distribution, is achieved by controlled hydrolysis and condensation of metal acetylacetonate and zirconiumn-propoxide mixtures. 15,16 In this context, solid state electrochemistry, using the voltammetry of microparticles (VPM) methodology, [17][18][19] can offer information on the oxidation state, coordinative environment 20 and electrocatalytic properties [21][22][23] of this kind of materials. In particular, application of VMP to doped zirconias and zircons has been revealed as a useful strategy for enhance selectivity toward electrochemical reduction/oxidation of selected analytes, as indicated in previous works.…”
mentioning
confidence: 99%